Facts, values and morality - Brandt, Richard B. 1910-1997 (Cambridge Univ. Press, 1996)
Richard Brandt is one of the most influential moral philosophers of the second half of the twentieth century. He is especially important in the field of ethics for his lucid and systematic exposition of utilitarianism. This new book represents in some ways a summation of his views and includes many useful applications of his theory. The focus of the book is how value judgments and moral belief can be justified. More generally, the book assesses different moral systems and theories of justice, and considers specific problems such as the optional level of charity and the moral tenability of the criminal law.